The role of extracellular Tau in the spreading of neurofibrillary pathology - Medina, Miguel; Avila, Jesús (Frontiers in Cellular Neuroscience, 2014)
The microtubule-associated protein tau plays a critical role in the pathogenesis of Alzheimer's disease (AD) and several related disorders collectively known as tauopathies. Development of tau pathology is associated with progressive neuronal loss and cognitive decline. In the brains of AD patients, tau pathology spreads following an anatomically defined pattern. Mounting evidence strongly suggests that accumulation of abnormal tau is mediated through spreading of seeds of the protein from cell to cell and point at the involvement of extracellular tau species as the main agent in the interneuronal propagation of neurofibrillary lesions and spreading of tau toxicity throughout different brain regions in these disorders. That would support the concept that pathology initiates in a very small part of the brain many years before becoming symptomatic, spreading progressively to the whole brain within 10-20 years. Understanding the precise molecular mechanism underlying tau propagation is crucial for the development of therapeutics for this devastating disorder. In this work, we will discuss recent research on the role of extracellular tau in the spreading of tau pathology, through synaptic and non-synaptic mechanisms.